PERSEPSI PEGAWAI TENTANG PEMBINAAN KINERJA PEGAWAI DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KOTA BUKITTINGGI - RENSI ELVIA RAHMI (Universitas Negeri Padang, 2016)
This research was motivated by to find out how employee perceptions about the coaching staff performance at the Department of Education, Youth and Sports of Bukittinggi. The purpose of this study was to obtain an overview of: (1) the coaching responsibilities of employees, (2) fostering the creativity of employees, (3) pembinan cooperation of employees, (4) fostering employee motivation in the Ministry of Youth and OlahragaKota Bukittinggi.This research is descriptive. The study population was all employees of the Department of Education Youth and Sports Bukittinggi totaling 104 people. While the samples are 58 people who where captured by Cochran formula. The sampling technique using Proportionate stratified random sampling technique. The instrument of this study was a questionnaire compiled in the form of 5 Likert scale with five (5) alternative answers are always (SL), often (SR), sometimes (KD), rarely (JR), never (TP) that have been tested validity and reliability.